Cortisol Directly Stimulates Spermatogonial Differentiation, Meiosis, and Spermiogenesis in Zebrafish (Danio rerio) Testicular Explants - Tovo-Neto, Aldo (Biomolecules, 2020)
Cortisol is the major endocrine factor mediating the inhibitory effects of stress on vertebrate reproduction. It is well known that cortisol affects reproduction by interacting with the hypothalamic–pituitary–gonads axis, leading to downstream inhibitory and stimulatory effects on gonads. However, the mechanisms are not fully understood. In this study, we provide novel data demonstrating the stimulatory effects of cortisol on spermatogenesis using an ex vivo organ culture system. The results revealed that cortisol treatment did not modulate basal androgen production, but it influenced transcript levels of a selected number of genes involved in the zebrafish testicular function ar (androgen receptor), star (steroidogenic acute regulatory), cyp17a1 (17α-hydroxylase/17,20 lyase/17,20 desmolase), cyp11a2 (cytochrome P450, family 11, subfamily A, polypeptide 2), hsd11b2 (11-beta hydroxysteroid dehydrogenase), cyp2k22 (cytochrome P450, family 2, subfamily K, polypeptide 22), fkbp5 (FKBP prolyl isomerase 5), grα (glucocorticoid receptor alpha), and grβ (glucocorticoid receptor beta) in a short-term culture. We also showed that cortisol stimulates spermatogonial proliferation and differentiation in an androgen independent manner as well as promoting meiosis and spermiogenesis by increasing the number of spermatozoa in the testes. Moreover, we demonstrated that concomitant treatment with RU 486, a potent glucocorticoid receptor (Gr) antagonist, did not affect the cortisol effects on spermatogonial differentiation but blocked the induced effects on meiosis and spermiogenesis. Supporting the Gr-mediated effects, RU 486 nullified the cortisol-induced expression of sycp3l (synaptonemal complex protein 3), a marker for the meiotic prophase that encodes a component of the synaptonemal complex. This is consistent with in silico analysis that found 10 putative GREs (glucocorticoid response elements) upstream of the zebrafish sycp3l. Finally, we also showed that grα mRNA is expressed in Sertoli and Leydig cells, but also in several types of germ cells, including spermatogonia and spermatocytes. Altogether, this evidence indicates that cortisol exerts paracrine roles in the zebrafish testicular function and spermatogenesis, highlighting its effects on spermatogonial differentiation, meiosis, and spermiogenesis.